Thinking In Islamic Legal Philosophy In Conflicts On Justice Of Women's Inheritance Rights - Sagala, Siti Rahma; Meisya, Meisya; Batubara, M. Ismail; Lingga, Nauval Salman (Kitabah: Jurnal Pendidikan Sosial Humaniora, 2024)
In Islamic law, inheritance is defined as the law that regulates the transfer of ownership rights to the inheritance of the heir and anyone who has the right to become an heir and their respective shares. This is clearly regulated in various sources, namely the Al-Quran and Hadith, the Compilation of Islamic Law is a collection of applied laws that apply in the Religious Courts as a guide for judges in carrying out their duties. The type of research used is normative legal research which uses normative case studies in the form of legal products. The data used is secondary data, in the form of library documents which include official documents, library books, scientific works, articles and documents related to the research material. According to the Qur'an, inheritance is based on farÄ'iá¸ in a bilateral model system and not a patrilineal model. In the study of Islamic legal philosophy, humans are legal subjects. The concept of inheritance share 2:1, in TafsÄ«r FÄ« DzilÄlil Qur'an, Sayyid Qutb explains that the problem of 2:1 for men and women is justice because men's obligations are considered heavier than women's obligations. In terms of inheritance distribution, it is regulated in The Koran stipulates that the division between men and women is two parts of women which we must obey, so Allah has his own command, if we think about it, it could be that the part of a man is bigger because he will have a family, namely children, a wife who is responsible for living.